Multisensory Imagery 2012
DOI: 10.1007/978-1-4614-5879-1_19
|View full text |Cite
|
Sign up to set email alerts
|

Mental Imagery and Psychopathology: Examples of Post-traumatic Stress Disorder and Bipolar Disorder

Abstract: This chapter aims to provide an update on the relation between mental imagery and psychopathology, with particular reference to post-traumatic stress disorder and bipolar affective disorder. Current evidence is provided to give an overview of the strengths and limitations of existing cognitive behavioural therapies for these two psychological disorders. Clinical vignettes are used to illustrate how imagery interventions may be incorporated into cognitive behavioural therapy to enrich the array of treatment str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 94 publications
0
6
0
1
Order By: Relevance
“…Although quantitative studies have considered some aspects of thought style, such as verbal fluency, that line of pursuit has not been particularly successful (Johnson et al, 2012), and it would seem fruitful for researchers to consider a broader range of constructs to quantify non-linearity or non-conventionality. Possible directions would include examining use of more unconventional reference points, mind-wandering (Baird et al, 2012), schizotypal, and other unusual thought styles that have been shown to benefit creativity (Folley & Park, 2005), and imagery (Ng, Krans, & Holmes, 2013). On the whole, researchers need new paradigms for considering the cognitive features that promote creativity within BD.…”
Section: Discussionmentioning
confidence: 99%
“…Although quantitative studies have considered some aspects of thought style, such as verbal fluency, that line of pursuit has not been particularly successful (Johnson et al, 2012), and it would seem fruitful for researchers to consider a broader range of constructs to quantify non-linearity or non-conventionality. Possible directions would include examining use of more unconventional reference points, mind-wandering (Baird et al, 2012), schizotypal, and other unusual thought styles that have been shown to benefit creativity (Folley & Park, 2005), and imagery (Ng, Krans, & Holmes, 2013). On the whole, researchers need new paradigms for considering the cognitive features that promote creativity within BD.…”
Section: Discussionmentioning
confidence: 99%
“…The study provides preliminary evidence that mental imagery susceptibility could be a cognitive marker worth exploring in future studies with larger sample sizes and high familial risks for bipolar disorders and with longer follow-up periods. Investigating mental imagery (in addition to verbal thoughts) may be useful in developing psychological treatments for bipolar disorder, for example, in the area of Cognitive Behavioural Therapy ( Ng et al, 2013 ; Stratford, Cooper, Di Simplicio, Blackwell, & Holmes, 2015 ), and in psychiatry more generally ( Di Simplicio, McInerney, Goodwin, Attenburrow, & Holmes, 2012 ). This study provides just one step in that direction.…”
Section: Clinical Implications and Conclusionmentioning
confidence: 99%
“…There has been a recent call for research investigating the contribution of cognitive and emotional factors associated with risk for bipolar disorders ( Johnson, 2005 ). One such potential cognitive factor is mental imagery susceptibility ( Holmes, Geddes, Colom, & Goodwin, 2008 ; Ng, Krans, & Holmes, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, MI is associated with psychophysiological responses (15), which suggest active processing of motor representations. Heightened motorsensory, psychophysiological, and emotional information during MI may mask conceptual processing of events and increase the likelihood and frequency of intrusive imagery (16). Interestingly, psychophysiological responses can provide an adjunct measure of symptom severity in PTSD (17).…”
Section: Advances In the Science Of Motor Imagery (Mi)mentioning
confidence: 99%